Mechanotherapy in restoration treatment of patients with the osteochondrosis of lumbar-sacrum department of spine - Авраменко [Ol’ga Avramenko] Олена Миколаївна (Slobozhanskyi Herald of Science and Sport, 2013)
Actuality problem of physical rehabilitation of patients with the osteochondrosis of spine is described by the author. The use of vehicles of mechanotherapy is considered in by a complex restoration treatment of patients with the neurological displays of lumbar-sacrum osteochondrosis. The program of physical rehabilitation is described for the men with radikuloishemiy L5-S1, which was worked out and inculcated in work of separation of restoration treatment of regional medical-athletic dispensary. Efficiency of the offered program of restoration treatment is appraised on the basis of study and analysis of dynamics of neurological status, data of rheovasography and goniometrys.